Smooth-to-rough morphotype switching, a mechanism of phage resistance in Mycobacterium abscessus - Jun Hao Liew; Ayuni Norman; Morgane Illouz; Teck-Hui Teo; Riccardo Delli Ponti; Claire Hamela; Lalit Mohan; Renee Lew; Chanvutha Ron; Kay En Low; Wassim Daher; Aryeh Chiam; et al. (Proceedings of the National Academy of Sciences, 2026)
Mycobacterium abscessus infections represent a growing global health concern due to their severe pathology and difficulty of treatment, largely driven by their intrinsic antimicrobial resistance. While phage therapy has emerged as a promising alternative approach, studies have predominantly focused on glycopeptidolipids (GPL)-deficient M. abscessus rough variants instead of the GPL-producing smooth variants predominant in Asia. Here, we aim to develop phage cocktails targeting both smooth and rough morphotypes. In the process, we found that phage treatment of smooth variants can select for rough morphotype switching from smooth-to-rough variants in vitro and in vivo, resulting in phage resistance associated with mutations within the GPL biosynthetic locus. We validated our findings in vitro and in vivo, suggesting a two-layered phage combination that surpasses single-phage treatments and potentially improves clinical phage cocktail strategies. This work underlines the need to better understand mechanisms of phage resistance in phage therapy and associated potential adverse effects and solutions. Phage resistance in M. abscessus through morphotype switching is clinically significant, as it may complicate treatment outcomes but could be averted with proper phage combinations.